KETERAMPILAN MENGAJAR DAN KEDISIPLINAN GURU DALAM PEMBELAJARAN KEWARGANEGARAAN SISWA SMAN 1 KADEMANGAN - Arief Heryprabawa (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2016)
This study aims to see the effect of teaching skills and teachers ’ discipline to improve students ’ achievement in civic education subject. This study used explanatory association design where data were analyzed using multiple liniar regression. The study was conducted at SMAN 1 Kademangan Blitar and involved 63 students as sample. The study revealed: (a) teachers ’ skill to teavh Civic Education was high proficiency, (b) students ’ discipline in learning Civic Education was good, (c) students performed very good attitude in certain environment that annoyed learning process they faced, (d) analysis using t-test indicated that variables of learning motivation, learning discipline and intelligence partially affected students ’ achievement on Civic Education subject in the level of significance up to 99%. Simultaneously, the hypothesis testing proved that variables of teacher skills and teachers ’ discipline to teach, altogether affected students ’ achievement.